Tribological behaviors of graphite sliding against cemented carbide in CaCl2 solution. (6th October 2015) - Guo, Fei; Tian, Yu; Liu, Ying; Wang, Yuming
Abstract: The tribological behaviors of graphite sliding against cemented carbide were investigated using a standard tribological tester Plint TE92 in a ring-on-ring contact configuration in both CaCl2 solution and deionized water. An interesting phenomenon occurred: as the CaCl2 solution concentration increased, the friction coefficient firstly decreased and was lower than that in the deionized water, and then gradually increased, exceeding the friction coefficient in the deionized water. The wear rate of the, graphite also presented the same variation trend. According to the polarization curves of cemented carbide, contact angle measurements, Raman spectrum analysis and scanning electron microscope (SEM) images analysis, the above friction and wear behaviors of graphite sliding against cemented carbide were attributed to the graphite surface wettability and the cemented carbide surface corrosion property.